2020
DOI: 10.1007/s42452-020-2186-5
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of chitin and chitosan from Termitomyces titanicus

Abstract: This research focuses on the extraction and characterisation of chitin and chitosan from fungal biomass, Termitomyces titanicus, by immersing it in a solution of sodium hydroxide, followed by deacetylation in a basic medium using the full two-level factorial design (2 2) to obtain chitosan as a residual. The obtained chitosan was characterised by basic conductimetric titration and viscometry to determine the degree of deacetylation and the average molecular weight, respectively. The extraction of chitin was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
(21 reference statements)
0
13
1
Order By: Relevance
“…Chitosan from the fungi Aspergillus niger has also been reported with a 90 % DD [19], this value is higher than the values obtained in this study. However, chitosan from Termitomyces titanicus had degree of deacetylation (69.50 %) lower than was reported in the present work [20]. These discrepancies in degree of deacetylation might be due to variation in mushroom species.…”
Section: Figure 3 Percentage Yield Of Chitosan Derived From P Ostreat...contrasting
confidence: 83%
“…Chitosan from the fungi Aspergillus niger has also been reported with a 90 % DD [19], this value is higher than the values obtained in this study. However, chitosan from Termitomyces titanicus had degree of deacetylation (69.50 %) lower than was reported in the present work [20]. These discrepancies in degree of deacetylation might be due to variation in mushroom species.…”
Section: Figure 3 Percentage Yield Of Chitosan Derived From P Ostreat...contrasting
confidence: 83%
“…The NSF contained higher amounts of chitins than ergosterol doubling the levels found in the initial SP (Table 1) since these bres are not soluble in hot water. Only traces of chitosan were detected in both SP NSF and these low concentrations were also noticed before for shiitake and other mushroom species (Chien et al, 2016;John Kasongo et al, 2020;Savin et al, 2020). Therefore, the NSF was subjected to a deacetylation method using a hot alkaline medium to release acetyl groups of chitins.…”
Section: Enhancing the Chitosan Levels Of The Nsf Fractionmentioning
confidence: 64%
“…Moreover, chitosan and other dietary bres can also increase intestinal viscosity impairing cholesterol absorption (Silva et al, 2021). Regarding chitosan immune-modulating ability, it has shown potent immune-stimulatory effects by activating antigen-presenting cells and inducing cytokines secretion (Li et al, 2021) Although chitosan presence has been described in mushrooms, its content was signi cantly lower than chitin concentrations, particularly in shiitake mushrooms, being even undetectable in many cases (Chien et al, 2016;John Kasongo et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…A study by [ 59 ] reported that chitosan samples were extracted from white shrimp shells using 40% ( w / v ) and 60% ( w / v ) NaOH in the deacetylation step and the deacetylation degrees were 94.23% and 92.45%, respectively. The DD of chitosan extracted from fungal ( Termitomyces titanicus ) biomass was calculated using conductimetric titration and was observed to be 69.50% [ 60 ].…”
Section: Resultsmentioning
confidence: 99%